2015
DOI: 10.3390/ijms161226089
|View full text |Cite
|
Sign up to set email alerts
|

Linalool Induces Cell Cycle Arrest and Apoptosis in Leukemia Cells and Cervical Cancer Cells through CDKIs

Abstract: Plantaginaceae, a popular traditional Chinese medicine, has long been used for treating various diseases from common cold to cancer. Linalool is one of the biologically active compounds that can be isolated from Plantaginaceae. Most of the commonly used cytotoxic anticancer drugs have been shown to induce apoptosis in susceptible tumor cells. However, the signaling pathway for apoptosis remains undefined. In this study, the cytotoxic effect of linalool on human cancer cell lines was investigated. Water-soluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 41 publications
6
47
0
Order By: Relevance
“…4d). A recent study identified p27 as an important cyclin-dependent kinase inhibitor that inhibits the activation of cyclin D-CDK4 complexes and induces cell cycle arrest at the G0/G1 and G2/M phases [18]. In addition, Akt pathway regulates cell cycle progression and cell proliferation by influencing p27, and the results presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4d). A recent study identified p27 as an important cyclin-dependent kinase inhibitor that inhibits the activation of cyclin D-CDK4 complexes and induces cell cycle arrest at the G0/G1 and G2/M phases [18]. In addition, Akt pathway regulates cell cycle progression and cell proliferation by influencing p27, and the results presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been demonstrated that linalool can induce the cell cycle of U937 cells to arrest at the G0/G1 phase, while HeLa cells arrest at the G2/M phase, and its function facilitates the expression of p53, p21, p27, p16 and p18 (CDKIs) and the non-expression of CDK activity (Chang et al, 2015). Therefore, linalool can inhibit the cell cycle of leukemia cells and cervical cancer cells, and it could thus be used to arrest cell cycle of osteoclast and to develop novel therapeutic agents for periodontal disease.…”
Section: Discussionmentioning
confidence: 99%
“…bungeana [201] trans-Sabinene hydrate (64) Z. clinopodioides subsp. rigida (0.1%) [21] Antiviral (HSV-1) [282] Moderate repellent (against tick Amblyomma americanum) [305] Z. tenuior [94] Anti-inflammatory (in carrageenan-induced edema and inhibition of hyperalgesia induced by L-glutamate and prostaglandin E2 in rats) [311]; anti-inflammatory (through inhibition of the expression of TNF-α and IL-6 in LPS-stimulated RAW 264.7 cells) [312]; antiinflammatory (in cigarette smoke-induced ALI in mice through inhibiting NF-κB activation) [313] Cytotoxic (human amelanotic melanoma cell line C32, renal cell adenocarcinoma ACHN, hormone-dependent prostate carcinoma LNCaP) [314]; induction of apoptosis (variety of human leukaemia cells) [315][316][317] Hypocholesterolemic (through inhibition of HMG-CoA reductase and conversion of lanosterol to cholesterol) [318,319] Protective effect against t-BOOH induced mutagenesis [194] Review on some effects on cardiovascular system [221] Sedative and anxiolytic [320]; antidepressant [321]; GABAA receptor modulation [322] OH Z. clinopodioides subsp. rigida [21] Z. tenuior [94] p-Menth-3-en-8-ol (65)…”
Section: Ohmentioning
confidence: 99%
“…rigida [21] Z. clinopodioides subsp. rigida (12.5%) [21] Z. tenuior (53.97%) [179] Linalool ( Anti-inflammatory (in carrageenan-induced edema and inhibition of hyperalgesia induced by L-glutamate and prostaglandin E 2 in rats) [311]; anti-inflammatory (through inhibition of the expression of TNF-α and IL-6 in LPS-stimulated RAW 264.7 cells) [312]; anti-inflammatory (in cigarette smoke-induced ALI in mice through inhibiting NF-κB activation) [313] Cytotoxic (human amelanotic melanoma cell line C32, renal cell adenocarcinoma ACHN, hormone-dependent prostate carcinoma LNCaP) [314]; induction of apoptosis (variety of human leukaemia cells) [315][316][317] Hypocholesterolemic (through inhibition of HMG-CoA reductase and conversion of lanosterol to cholesterol) [318,319] Protective effect against t-BOOH induced mutagenesis [194] Review on some effects on cardiovascular system [221] Sedative and anxiolytic [320]; antidepressant [321]; GABA A receptor modulation [322] Analgesic activity reviewed [199] Review on metabolism and toxicity [200] Molecules 2016, 21, 826 20 of 53 [296]; antioxidant [273,[297][298][299] Review on some effects on cardiovascular system [221] Gastroprotective effects in the acute and chronic ulcer models in rats [300] Positive allosteric modulator of the GABAA receptors in primary cultures of mouse cortical neurons [301] Anti-hyperglycemic and anti-hyperlipidemic activity in high fat-induced type 2 diabetic C57BL/6J mice [302] and protective effect in nephropathy [303] Analgesic activity reviewed [199] Review on metabolism and toxicity [200]; general review on thyme and 62 [304] cis-Sabinene hydrate …”
Section: Ohmentioning
confidence: 99%